Penyuluhan Hukum: Penanggulangan Kekerasan Seksual Terhadap Perempuan Dan Anak Di Desa Oenuntono, Kecamatan Amabi Oefeto Timur, Kabupaten Kupang - Daud Yaferson Dollu; Jenny Ermalinda; Cyrilius Wilton Taran Lamatoro; Alexander Simon Pally (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In social life, cases of sexual violence against women and children often occur, especially sexual violence against children, the issuance of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, and Law Number 12 of 2014 2022 Concerning Crimes of Sexual Violence (TPKS), providing guarantees and protection to children and women as victims of fornication. The rise of acts of violence against children and women that have occurred recently in the form of physical, psychological and sexual violence, not receiving adequate legal protection and human rights, including low legal knowledge, is one of the factors that children and women often become victims of. . The frequent occurrence of criminal acts against children and women is one of the reasons the service team is conducting community service in the form of free legal counseling for the community in Oenuntono Village, East Amabi Oefeto District, Kupang Regency. One of the backgrounds of the community service team in Oenuntono Village is that higher education institutions are obliged to organize education and teaching, research, and community service. According to the law on higher education, community service is an activity of the academic community that utilizes science and technology to advance social welfare and educate the nation's life. This activity aims to carry out the Tri Dharma of Higher Education. This service uses the counseling method, and free sharing of legal knowledge which is carried out by presenting materials related to sexual violence against women and children, to residents of the Oenuntono village community, Amabi Oefeto Timur District, Kupang Regency, by a team of devotees from Faculty of Law, University of Nusa Cendana, Kupang. Based on the results of the service implementation, it can be concluded that; 1. Residents of the village of Oenuntono, Amabi Oefeto Timur District, Kupang Regency, are members of the community who are law savvy. 2. The people of Oenuntono Village, East Amabi Oefeto District, apparently have many problems related to the law, (especially sexual violence against women and children). Residents of the Oenuntono village community, Amabi Oefeto Timur District really need adequate information and legal knowledge related to rules related to sexual violence against women and children so they can know the steps in taking legal action if sexual violence against women and children occurs 4. The presence of a service team can make a positive contribution in terms of providing free legal understanding for the people of Uenuntono village, Amabi Oefeto Timur District, through legal counseling activities.